ISSUES ON RESTRUCTURING OF A FINANCING FACILITY IN MALAYSIAN ISLAMIC BANKS - Muneem, Abdul; Mohd Razif, Nor Fahimah; Ali, Abdul Karim (Jurnal Syariah, 2020)
The restructuring of a financing facility in Malaysian Islamic banks provides assistance to customers facing financial hardships. However, the facility arises some Sharīʿah concerns like qalb al-dayn (debt restructuring), imposing new selling price and profit, and using a current asset for new contracts. The research aims to examine the current practice of restructuring of financing facilities and to identify the issues and challenges in this facility in Malaysian Islamic banking institutions. To fulfill the objectives of this research, a qualitative approach is adopted to achieve the theoretical background of the study and interviews conducted to obtain practical views of the subject matter. The study finds that the increase in a new contract over the existing contract generates ribā. In addition, the ownership of the commodity has to be transferred in a new contract to conclude a contract, however, the ownership is not transferred in the practice of restructuring of financing facility. Finally, the restructuring of a financing facility is similar to qalb al-dayn which is non-Sharīʿah compliant according to the majority of scholars. The study suggests resolving those issues before offering such a facility to the customers will not result in non-Sharīʿah compliant issue and alternatively, the Islamic banks may offer rescheduling of financing facility instead of restructuring.